Analiza učinkovitosti branjenja rokometnih vratarjev na evropskih prvenstvih v obdobju od 2010 do 2020 glede na končno uvrstitev reprezentanc - Marinček Ribežl, Miša (Šport (Ljubljana), 2022)
The main purpose of our research is to determine the efficiency of goalkeeper defense at the European Men‘s Championships from 2010 to 2020, especially whether they contain statistically significant differences between those teams that won medals in bellow ranked teams. Official data from the EHF (eurohandball.com) are used. A quantitative method is used for the analysis; data are processed with the SPSS program; differences were determined using Mann-Whitney test; correlation with the Spearman coefficient. The data show that there are statistically significant differences in defensive efficiency between the goalkeepers of the first three ranked national teams and all others; especially in the total number of defenses (Sig=0.000), in the total number of shots received (Sig=0.001) and also in the total efficiency (%) (Sig=0.004). The greatest correlation of goalkeeper efficiency with the final ranking is achieved for shots from a distance of more than 9m (r=-0.444; Sig=0.000). Based on the results, we can confirm the thesis that the efficiency of the handball goalkeeper‘s defense has one decisive influence on the final ranking of the national teams and that defending from distance 9 m or more is one of the key factors.
Keywords: analiza igre; evropska prvenstva; obramba; rokomet; šport; športne reprezentance; vratarji (šport)